Targeting the AGEs-RAGE axis: pathogenic mechanisms and therapeutic interventions in diabetic wound healing - Lin, Haohui; Yang, Yi; Wang, Xia; Chung, Manhon; Zhang, Li; Cai, Sa; Pan, Xiaohua; Pan, Yu (Frontiers in Medicine, 2025)
Diabetes is a global health problem, with diabetic wounds constituting one of its most severe complications. Advanced glycation end products (AGEs) and their receptor, the receptor for advanced glycation end products (RAGE), play a key role in the pathogenesis of diabetic wounds. Accumulated AGEs bind to RAGE, activating various inflammatory and oxidative stress pathways such as NF-κB, PI3K-AKT, and JAK–STAT signaling, impairing normal wound healing. This review describes mechanisms by which the AGEs-RAGE axis disrupts vascular function, immune regulation, and cellular regeneration, thereby driving the formation of chronic non-healing wounds. Furthermore, we discuss emerging therapeutic strategies targeting the AGEs-RAGE axis, such as selective RAGE inhibitors, monoclonal antibodies, gene-based interventions, and AGE scavengers, highlighting their potential to enhance the treatment of diabetic chronic wounds.